2021
DOI: 10.3390/met11030491
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Control of the Interface Layer for Strength Enhancement of Dissimilar Al/Cu Joints via Ni Addition during TIG Arc Brazing

Abstract: Dissimilar metal joining between Al and Cu is effective for reducing the weight and cost of electrical components. In this study, dissimilar lap joining of pure Al to pure Cu with an Al-Ni filler material was conducted using tungsten inert gas (TIG) arc brazing, and the effect of Ni on the joint strength associated with the microstructure of the intermetallic compound (IMC) layer at the dissimilar interface was examined. The addition of Ni effectively increased the interfacial strength of the joints. Regardles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The thickness of the IMC layer with 3 at.% Ni was 2.4 µm, while without Ni, it was 1.4 µm, indicating that the addition of 3 at.% Ni increased the thickness of the IMC layer. In contrast, it was reported that an IMC layer thicker than 30 µm formed at the interface of an Al/Cu weld produced via GTAW with 2.3 at.% Ni [28]. Because FSW is a low-heat-input joining process, it effectively reduces the thickness of the IMC layer.…”
Section: Interfacial Microstructurementioning
confidence: 96%
See 4 more Smart Citations
“…The thickness of the IMC layer with 3 at.% Ni was 2.4 µm, while without Ni, it was 1.4 µm, indicating that the addition of 3 at.% Ni increased the thickness of the IMC layer. In contrast, it was reported that an IMC layer thicker than 30 µm formed at the interface of an Al/Cu weld produced via GTAW with 2.3 at.% Ni [28]. Because FSW is a low-heat-input joining process, it effectively reduces the thickness of the IMC layer.…”
Section: Interfacial Microstructurementioning
confidence: 96%
“…The phases on the fracture surfaces were examined using X-ray diffraction (XRD) to identify the fracture location of the weld. [28] reported that the addition of 2.3 at.% Ni to the Al/Cu weld produced by GTAW exhibited the most effective improvement in the weld strength, reaching 50 MPa. Therefore, the strength of the Al/Cu weld produced by FSLW was higher than that of the weld produced by GTAW.…”
Section: Microstructure Examinationsmentioning
confidence: 99%
See 3 more Smart Citations